EFFECT OF THERMAL VARIATION ON SOME HAEMATOLOGICAL VALUES OF SCHIZOTHORAX PLAGIOSTOMUS (HECKEL) - BHAIT, S. N.; SINGH, H. R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1985)
Laboratory acclimatized fishes (20.5°C), when transferred to low and higher temperatures (2-4°C and 30°C), exhibited marked behavioural response. They swam rapidly with lashing movement of their tail for about 7-17 minutes, after which they became quiescent. However, the fish did not show any change to their behaviour when transfered at 17°C At 2-4°C water temperature the TEC, Hb and PCV values of S. plagiostomus fell significantly (P<0.001); TLC value as well as MCH and MCV values did not change. Differential leucocyte counts showed no marked variation when compared to controls at 20.5°C. No. appreciable changes in these parameters (Hb and PCV) were noticed at 30°C, except significant decrease in the TEC and MCHC values and increase in TLC, MCH and MCV values. Haemolysis and crenated cells were noted at 2 4°C and 30°C respectively.